INTEGRATING TECHNICAL AND COMMUNITY TRAINING FOR SOLAR ENERGY ADOPTION: A CASE STUDY OF BARENGKOK VILLAGE - Sri Hastuty; Yudi Rahmawan; Khusnun Widiyati; Yose Fachmi Buys; Iman Kartolaksono Reksowardojo; Syuja Lagusma; Fayza Yulia (Jurnal Bakti Masyarakat Indonesia, 2026)
Access to clean and sustainable energy remains limited in rural Indonesia, constraining social and economic activities. To address this issue, a community-based program was conducted in Barengkok Village, Bogor Regency, focusing on the installation, socialization, and maintenance training of solar photovoltaic (PV) street lighting systems. The program aimed to promote renewable energy awareness and strengthen local capacity for sustainable energy management. A participatory approach was applied, integrating three activities: installation of solar PV lamps at strategic sites, education on clean energy and carbon footprint reduction, and hands-on maintenance training. Program evaluation involved pre- and post-tests, observations, and participant satisfaction surveys. Results showed a clear improvement in participants’ understanding and technical competence. Average scores for PV knowledge and carbon awareness increased from 68.48% to 75.00%, Furthermore, 96% of the participants expressed high satisfaction. This initiative demonstrates that community-based renewable energy education effectively enhances technical literacy, supports carbon reduction goals, and fosters long-term energy sustainability in rural areas.